Dari Alkitab ke Al-Qur’an : Transformasi Kisah Yusuf dalam Perspektif Intertekstualitas Julia Kristeva - Ummu Salamah Al-Hasyimi; M. Iqbal Arrasid; Yulia Alya Putri (STIKes Ibnu Sina Ajibarang, 2025)
This study examines the narrative transformation of the story of Joseph in the perspective of Julia Kristeva's intertextuality through a comparative analysis between Genesis 37-50 (Bible) and Surah Yusuf (Qur'an). This study aims to: (1) identify patterns of text adaptation, (2) analyze the mechanism of narrative transmission, and (3) reveal the theological implications of the intertextuality process. The research method uses a qualitative approach with comparative textual analysis techniques. The data were analyzed through three stages: (1) identification of text parallels, (2) mapping of narrative transformation (including reduction, amplification, and re-emphasization), and (3) interpretation of theological impact. The study is strengthened by referring to authoritative commentaries from both traditions. The results show three main findings: First, the Qur'ān simplifies the narrative (haplology) of the etiological and psychological elements found in the biblical version. Second, there is an amplification of the divine aspects and moral values in the Qur'ānic version. Third, this transformation reflects an adjustment to the Islamic theological framework while maintaining the core prophetic message. This research contributes to the comparative study of scripture by showing how intertextuality operates in sacred space. The findings enrich the understanding of the transmission dynamics of the prophetic tradition in the heavenly religions.